PENINGKATAN PROFESIONALITAS PENGAJAR AGAMA DI ERA DIGITAL MENYONGSONG REVOLUSI 4.0 (Suatu Tinjauan PAK dalam Perspektif Pedagogik Kritis) - Wem. David. Rindengan (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2019)
This paper is a critique of the traditional pedagogic in education using the critical pedagogic concept formulated by George. S. Counts. Critical pedagogic seeks to view the need for a new social society that can cope with various distributions and regulatory needs through education. In the educational world the teacher's role in the school is an active cultural bearer instead of teaching a passive culture. In the context of religious teachers in this regard, will deal with methods of educating that must conform to the development of science and technology. Teacher/lecturer is the creator of the learning process is required to further improve professionalism so as to create a learning society that thinks past the boundaries of kinship, thinking to create a better future. A critical pedagogic concept formulated by George. S. Counts, referred to as "the necessity of a new social order" in the context of the contemporary education are religious teachers/lecturers need to get out of the face of the slave mentality, and consciously raise strength to gain the influence of reaching for power to Can do great goals in caring for mankind, and increase the sense of global responsibility. The authors realize that the learning process based on information and communication technology in Indonesia is not optimal but religious teachers should not only stop the understanding on social facts but then on social actions that can change Social reality becomes a new social order, which is professional religious teachers in the use of information and communication technologies. Keywords: traditional pedagogic, critical pedagogic, professionality, new Social Society order, Global